Using Fable In Audio Visual To Improve Listening Comprehension of The Students At The Eleventh Grade Of SMPN 3 Pitumpanua, Wajo - Tsamratul’aeni Tsamratul’aeni; Abdullah Syukur (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims at findings out whether or not the use of fables in audio-visual can improve listening comprehension of the students at SMPN 3 Pitumpanua. The researcher applied pre-experimental design. Population was the eleventh-grade students of SMPN 3 Pitumpanua. The number of populations is 120 students. The researcher applied cluster random sampling technique in determining 20 students as the sample of this research. The instrument of this research is listening test. The result of the research shows the students’ score in the pre-test is 43.00 and in the post-test is 72.00. It indicates that the use of fable in audio visual can improve listening comprehension of eleventh grade students of SMPN 3 Pitumpanua.